2017
DOI: 10.5005/jp-journals-10024-2037
|View full text |Cite
|
Sign up to set email alerts
|

Good Bugs vs Bad Bugs: Evaluation of Inhibitory Effect of Selected Probiotics against Enterococcus faecalis

Abstract: Introduction:The main goal of endodontics is the prevention of apical periodontitis. This is due to the presence of persistent pathogenic microorganisms, such as Enterococcus faecalis, and its ability to directly cause acute and chronic inflammation in the periapical tissues. Lactobacillus has been shown to promote health in the intestines as well as to inhibit the growth of certain problematic oral bacteria. This study explores shifting the established paradigm of endodontic treatment, which has focused on el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Microorganisms not only cause CAP but have also been used in the research of new treatments. For example, some studies have explored the inhibitory effect of probiotics on pathogenic bacteria in the root canal (Kumar et al, 2021), which may be used to identify pathogenic bacteria in the root canal for the purposes of treatment (Bohora and Kokate, 2017). The results of a comparative clinical trial showed that treatment with a probiotic product completely prevented the regeneration of biofilms formed by Enterococcus faecalis compared to low concentrations of sodium hypochlorite solution (Safadi et al, 2022).…”
Section: Probioticsmentioning
confidence: 99%
“…Microorganisms not only cause CAP but have also been used in the research of new treatments. For example, some studies have explored the inhibitory effect of probiotics on pathogenic bacteria in the root canal (Kumar et al, 2021), which may be used to identify pathogenic bacteria in the root canal for the purposes of treatment (Bohora and Kokate, 2017). The results of a comparative clinical trial showed that treatment with a probiotic product completely prevented the regeneration of biofilms formed by Enterococcus faecalis compared to low concentrations of sodium hypochlorite solution (Safadi et al, 2022).…”
Section: Probioticsmentioning
confidence: 99%
“…In vitro studies have demonstrated that certain probiotics exhibit inhibitory activity against endodontic pathogens (Bohora and Kokate, 2017a;Bohora and Kokate, 2017b). Probiotic Akkermansia muciniphila was revealed to reduce gingipain transcription by P. gingivalis, thereby decreasing inflammatory cell infiltration and alleviating alveolar bone loss (Huck et al, 2020).…”
Section: Alter the Composition And Virulence Of The Oral Microbiotamentioning
confidence: 99%
“…discovered that topical application of Bifidobacterium lactis HN019 reduced bone destruction, decreased the proportions of Veillonella parvula , Capnocytophaga sputigena , E. corrodens , and P. intermedia -like species, and increased the proportions of Actinomyces and Streptococcus -like species ( Oliveira et al., 2017 ). In vitro studies have demonstrated that certain probiotics exhibit inhibitory activity against endodontic pathogens ( Bohora and Kokate, 2017a ; Bohora and Kokate, 2017b ). Probiotic Akkermansia muciniphila was revealed to reduce gingipain transcription by P. gingivalis , thereby decreasing inflammatory cell infiltration and alleviating alveolar bone loss ( Huck et al., 2020 ).…”
Section: Factors That Affect Oral Microbiota-mediated Alveolar Bone Metabolismmentioning
confidence: 99%